Shiga Toxin 2a Binds to Complement Components C3b and C5 and Upregulates Their Gene Expression in Human Cell Lines - Sára Kellnerová (Toxins, 2021)
Enterohemorrhagic Escherichia coli (EHEC) infections can cause EHEC-associated hemolytic uremic syndrome (eHUS) via its main virulent factor, Shiga toxins (Stxs). Complement has been reported to be involved in the progression of eHUS. The aim of this study was to investigate the interactions of the most effective subtype of the toxin, Stx2a, with pivotal complement proteins C3b and C5. The study further examined the effect of Stx2a stimulation on the transcription and synthesis of these complement proteins in human target cell lines. Binding of Stx2a to C3b and C5 was evaluated by ELISA. Kidney and gut cell lines (HK-2 and HCT-8) were stimulated with varied concentrations of Stx2a. Subsequent evaluation of complement gene transcription was studied by real-time PCR (qPCR), and ELISAs and Western blots were performed to examine protein synthesis of C3 and C5 in supernatants and lysates of stimulated HK-2 cells. Stx2a showed a specific binding to C3b and C5. Gene transcription of C3 and C5 was upregulated with increasing concentrations of Stx2a in both cell lines, but protein synthesis was not. This study demonstrates the binding of Stx2a to complement proteins C3b and C5, which could potentially be involved in regulating complement during eHUS infection, supporting further investigations into elucidating the role of complement in eHUS pathogenesis.